A Comparative Expert-Based Analysis for Prioritizing Waqf Asset Optimization Strategies in Indonesia: An Analytic Network Process (ANP) Approach - Putra, Trisno Wardy; Alwahidin; Sikki, Kaisar Lahiya (Journal of Islamic Economics and Finance Studies, 2025)
Land waqf in Indonesia holds significant potential for economic empowerment; however, its predominantly conventional management practices have limited its contribution to broader development goals. This study aims to formulate comprehensive strategic priorities, based on expert evaluations, to enhance the sustainable effectiveness of land waqf management. The research employs the Analytic Network Process (ANP), a method that enables the analysis of interdependencies among decision elements using expert input. The results reveal notable differences in emphasis among expert groups. Regulators identify regulatory issues as the primary challenge (0.303) and the most critical solution area (0.321), with regulatory strengthening emerging as the top strategic priority (0.272). Academics consider nazhir-related issues as the central problem (0.344), advocating balanced empowerment of both wakif and nazhir (each 0.285), supported by strategies focused on enhancing waqf literacy and optimizing asset management (each 0.342). Practitioners also emphasize the role of nazhir (0.308) and prioritize capacity-building solutions for nazhir (0.311), proposing a comprehensive strategy encompassing waqf literacy, regulatory reinforcement, and asset optimization (each 0.270). These findings underscore the need for a multidimensional approach to waqf asset optimization—one that integrates institutional development, educational initiatives, and policy reform. The study highlights the critical importance of collaboration among regulators, academics, and practitioners to establish an effective, professional, and productive land waqf management system.